Pendampingan Pembelajaran Dasar Ilmu Tajwid di TPQ Sabilurrosyad - Muhammad Kris Yuan Hidayatulloh; Robithotul Ummah; Dita Meilawati; Egydia Savitri (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Community service activities through the basic learning of tajwid for TPQ students aim to: (1) help optimize learning in TPQ regarding correct recitation; (2) improving students' ability to understand recitation and tilawati methods; and (3) increasing the ability of teachers to teach using the Tilawati method.The target audience for the basic learning activities of tajwid is TPQ students in the Jombang district. This activity was carried out at the Al Qur'an Sabilurrosyad Education Park, Jombang with a total of about 40 people. This approach to implementing community service activities includes lectures, discussions, and questions and answers. Based on the results of these introductory activities, it can be concluded that the students at TPQ do not yet understand tajwid and tilawati. One of the difficulties is that learning that should use the tilawati method is not used thoroughly. In this introduction and learning activity, it was carried out by socialization (presentation) of questions and answers which was packaged in a Focus Group Discussion (FGD). From the results of this introductory activity, it can be seen that TPQ students are still confused with recitation. The introduction and deepening carried out by the executor approved by the TPQ was carried out with the aim that the basic understanding of the science of tajwid could penetrate the students and the deepening of the recitation method carried out could help TPQ students and teachers.